â€œThis Image of Themselvesâ€: (Re)Discovering the Merlionâ€™s Liminality - Chung, Singapore, Ian (Asiatic: IIUM Journal of English Language and Literature, 2013)
The publication by Singaporean small press Firstfruits Publications of Reflecting on the Merlion in 2009 marked a consolidation of the canon of Merlion poetry in Singapore. Apart from inspiring the work gathered in this anthology, Edwin Thumbooâ€™s â€œUlysses by the Merlionâ€ has also attracted both praise and criticism for its engagement with the Merlion. This essay seeks to establish a reading of Thumbooâ€™s poem using the concept of liminality, one that has previously been given little attention in the critical literature on the poem, despite being embedded in the text itself. It also argues that by ignoring this concept, the Merlion poems by Lee Tzu Pheng and Alfian Saâ€™at that followed after Thumbooâ€™s have had the unfortunate effect of forcing the discourse surrounding the Merlion into a dead end.